Induction and Socialization of New Teachers in Institutional Schools - Dhanapati Subedi; Beni Bahadur Karkee (The Open University of Sri Lanka, 2020)
The purpose of this paper is to explore how schools in Kathmandu practice the ideas of induction and socialization among new teachers appointed to the organization. The major focus is on exploring how newly hired employees become adjusted to the organization's culture, their work group, and how they learn the information necessary for effective job performance. The paper is developed on the basis of information collected through narrations shared during our interviews with administrators, human resource managers and teachers in the institutional schools of Kathmandu based on few guiding ideas like: framework institutions apply for teachers' induction and socialization during the transition and the issues and challenges inherent in the teacher induction process. In our engagement with the participants, we understood that the new entrants tend to struggle with their tasks; are seemingly nervous of the new work challenges, and tend to fail in conducting day-to-day activities in the absence of proper orientation about the job they are supposed to perform. Therefore, we conclude induction and socialization as strategic human resource management tools that help employees to connect to the new working environment through their head and heart. It could have direct influences on the quality of work expected from the new intake. Thus, it is undeniable that only those new intakes who are well oriented about organizational goals, who have prior information as to what is expected of them, who possess mechanisms to counter their early anxiety through familiarizing themselves with the working environment with the help of senior staff are able to deliver the service as per the expectation of the organization.